Zinc-Fortified Oral Rehydration Solution Improved Intestinal Permeability and Small Intestinal Mucosal Recovery. (June 2015) - Tran, Cuong D.; Hawkes, Joanna; Graham, Robin D.; Kitchen, Julie L.; Symonds, Erin L.; Davidson, Geoffrey P.; Butler, Ross N.
A randomized double-blind placebo-controlled study was conducted in children admitted to hospital with gastroenteritis (≥3 loose stools per day). All were treated for 5 days following admission with either zinc (Zn, 3 mg) or without Zn-fortified rice-based oral rehydration solution (ORS). 13 C-sucrose breath test (SBT) and intestinal permeability (lactulose/rhamnose or L/R ratio) were performed concurrently prior to commencement of ORS with or without Zn and at day 5 post-admission. There was a significant improvement in the SBT results in both the Zn-fortified group, median (5th-95th percentile) 2.1% (0.4% to 8.3%) versus 4.4% (0.4% to 10.4%), P < .05, and control group, 1.4% (0.1% to 5.4%) versus 4.3% (0.4% to 11.4%), P < .05, between the day of admission and day 5 post-admission. In the Zn-fortified group, there was also a significant improvement in L/R ratio between the day of admission and day 5 post-admission, 53.0 (19.5-90.6) versus 17.7 (13.4-83.2), P < .05. Low levels of Zn improved intestinal permeability but did not enhance short-term recovery following diarrheal illness.